Prevalence, characterisation and microbiological risk assessment of Bacillus cereus s.l. in ultra-high temperature chocolate milk - Anyi, Ubong (2019)
Ultra-high temperature chocolate milk is enjoyed by many due to its convenience, portability and it is also recognised for its delicious taste. The milk‟s sterilisation process is known to be able to inactivate microorganisms and bacterial spores and further prolong the milk‟s shelf life. However, despite the efficiency of sterilisation using UHT treatment, issues and outbreak regarding B. cereus in UHT milk were still reported. Hence, this study was conducted to evaluate the microbiological risk assessment of B. cereus s.l. in UHT chocolate milk. From this study, Bacillus spp. and B. cereus s.l. were detected in 31.11% and 24.30% out of 214 UHT chocolate milk samples respectively via MPN-PCR assay with MPN value ranged from less than 3 to more than 1100 MPN/ml. A total of forty-nine B. cereus s.l. isolates obtained were screened for the presence of toxin genes using PCR assay. The prevalence of diarrheagenic toxin genes bceT and nhe complex was 40.82% and 2.04% respectively, while the emetic toxin gene showed the prevalence of 20.41%. Clustering of B. cereus s.l. isolates based on Rep-PCR showed that the isolates were genetically diverse. This study also investigated the impact of temperature on B. cereus spore germination in UHT chocolate milk. Results showed that temperature played a significant role in B. cereus spore growth and germination. At 8 °C, there was no germination and growth of spores in UHT chocolate milk; at 25 °C and 35 °C, spore showed rapid germination and growth, in which germination and growth were more active at 35 °C. At the final stage of this study, an exposure assessment and risk estimate were modelled using @RISK software by incorporating all the risk factors studied in order to investigate the risk of consuming pathogenic B. cereus s.l.. The model estimated that incidence rate per 100,000 population in Malaysia was 0.1936 for emetic B. cereus s.l. with 181 expected cases and 0.1302 with 19 expected cases for diarrheagenic B. cereus. s.l.. In conclusion, these findings suggest the need for continuous supervision, routine maintenance and regular cleaning during production in order to minimize contamination, henceforth, lowering consumption risk of pathogenic B. cereus s.l..